1976
DOI: 10.1073/pnas.73.2.361
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Cibacron blue F3GA to proteins containing the dinucleotide fold.

Abstract: A simple, convenient, and sensitive spectrophotometric procedure is described for quantitative measurement of nucleoside phosphate binding sites constructed by the dinucleotide fold. The procedure involves difference spectral titration of such enzymes with the dye Cibacron blue F3GA in a spectral region remote from the intrinsic absorbance of proteins or natural ligands. The dehydrogenase, and glyceraldehyde-phosphate dehydrogenase, respectively. The concentrations of phosphoglycerate kinase and subtilisin w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
78
1

Year Published

1981
1981
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(81 citation statements)
references
References 19 publications
2
78
1
Order By: Relevance
“…The sensitivity of NADH:CCR to Cibacron blue 3GA indicated that the enzyme contains a pyridine-nucleotide binding site (23). NADH:CCR also contains (a) sulfhydryl group(s) sensitive to attack by the mercurial reagent mersalyl.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of NADH:CCR to Cibacron blue 3GA indicated that the enzyme contains a pyridine-nucleotide binding site (23). NADH:CCR also contains (a) sulfhydryl group(s) sensitive to attack by the mercurial reagent mersalyl.…”
Section: Discussionmentioning
confidence: 99%
“…Calmodulin is the eukaryotic protein that binds within a subdomain of the N terminus of B. pertussis ACT and stimulates its adenylate cyclase activity (51,92). To address this affinity issue, we evaluated binding of ACT to Blue-Sepharose, a reactive dye matrix that interacts with proteins through their nucleotide binding sites (54,80). This method has been previously utilized to determine ACT binding affinities based on the differential binding ability of ACT for Blue-Sepharose in the presence and absence of CaM (50).…”
Section: Reverse Transcription-pcr (Rt-pcr)mentioning
confidence: 99%
“…This is one of several triazine dyes which, when covalently linked to an insoluble porous support matrix such as agarose, is useful in the purification of a variety of enzymes (2,3,(8)(9)(10)12). The mode of purification by blue agarose affmity chromatography is comparable to purification by affmity chromatography in which the covalently linked ligand is a biological ligand, including, among others, substrates, cofactors, activators, antigens, antibodies, and competitive inhibitors.…”
mentioning
confidence: 99%